Elaboração e caracterização de chips de inhame ( Dioscoreaceae ). - Silva, Gabryella Aureliano Abreu da (2019)
The yam is a monocotyledon angiosperm plant of the Dioscoreaceae family, of the genus Dioscorea and has on average 150 to 200 species. It is widely consumed in Brazil, mainly in the northeast, with 90% of its production. This raw material is important socioeconomically because it is cultivated by family farmers, generating employment and income. Even in the face of various technologies and innovations, post-harvest losses of yams are still strongly present in the current context, largely due to inadequate storage and transport, as well as commercialization of this product without any processing. In this way, the alternative to elaborate products based on the yam appears as a way of greater utilization and value added to the raw material. The current population is seeking a healthy and at the same time fast and ready for consumption, then the idea of the elaboration of yams chips as a way to meet these demands in a single product. Therefore, the objective of this study was the elaboration of yam chips and analysis of their physical-chemical and sensorial characteristics, analyzing the acceptance index and purchase intention. For the elaboration of the chips, four formulations with different seasonings were developed: sample A = chips seasoned with onion, curry and salt; sample B = chips seasoned with onion, smoked paprika and salt; sample C = chips seasoned with onion, spicy paprika and salt; sample D = chips seasoned with onion, lemon pepper and salt. For the physical-chemical analysis of moisture, it was observed that as the chips were submitted to the drying process, their humidity decreased by 90%, consequently their water activity also decreased from 0.99 to 0.47. The yams chips, due to not being submitted to the frying process, presented very low values of lipids. Regarding sensory analysis, the products obtained an acceptance rate above 70% for almost all attributes, except flavor, for which only sample D obtained such index. The preference for sample D was also verified in the intention to buy, with 53%. In view of this, it is concluded that yams chips seasoned especially with lemon pepper have market potential.